The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000488776
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Induced Fetal Hypothyroidism: Diagnosis and Treatment with Intra-Amniotic Levothyroxine

Abstract: Background: Iodine is necessary for fetal thyroid development. Excess maternal intake of iodine can cause fetal hypothyroidism due to the inability to escape from the Wolff-Chaikoff effect in utero. Case Report: We report a case of fetal hypothyroid goiter secondary to inadvertent excess maternal iodine ingestion from infertility supplements. The fetus was successfully treated with intra-amniotic levothyroxine injections. Serial fetal blood sampling confirmed fetal escape from the Wolff-Chaikoff effect in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 43 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Fetal goiter is a rare condition that results of either fetal hypothyroidism or hyperthyroidism. It can cause several complications 5 and has several etiologies: congenital dyshormonogenesis, deficiency or excess of iodine or transplacental passage of maternal TRAb or ATD 6 . Maternal Graves’ disease accounts for more than 60% of fetal goiter 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Fetal goiter is a rare condition that results of either fetal hypothyroidism or hyperthyroidism. It can cause several complications 5 and has several etiologies: congenital dyshormonogenesis, deficiency or excess of iodine or transplacental passage of maternal TRAb or ATD 6 . Maternal Graves’ disease accounts for more than 60% of fetal goiter 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The Table 2 summarizes the therapeutic management, laboratory results, short‐ and long‐term outcomes of 21 cases reports of non‐immune hypothyroidism fetal goiter during the last ten years 6,31‐45 . Finally, IAIs likely prevented the hearing loss in a fetus with iodine‐induced hypothyroidism, highlighting the impact of prenatal TH substitution on complications 46,47 …”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In cases of fetal thyroid dysfunction, it seems that placental deiodinases are inhibited and, moreover, the intracellular activation to triiodothyronine in the fetal brain activated, protecting the brain from permanent damage (Girling 2003 ). Nevertheless, it has also been reported that only transient hypothyroidism can impair the long-term mental development of the children or cause hearing impairments (Derksen-Lubsen et al 1996 ; Kempers et al 2006 ; Jourdain et al 2010 ; Overcash et al 2016 ), and screening at birth with postnatal treatment may not be sufficient to ascertain unimpaired neurodevelopment (Hardley et al 2018 ). Therefore, the potential risks of side effects on the fetus resulting from iodine blockade should not be underestimated.…”
Section: Discussionmentioning
confidence: 99%